Exploring the Representation of Schizophrenia in the Main Character of the Black Swan Script - Yoana Gita Pradnya Lengari; Ade Daniel Patty (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores the portrayal of mental illness, particularly paranoid schizophrenia, in the film script “Black Swan.” Library research method is adopted for this study. The primary source material is the “Black Swan” script, and the secondary sources include theoretical reference books that provide supporting evidence for the analysis. Utilizing a psychological approach, the analysis explores the character of Nina Sayers and her descent into a mental breakdown. The paper examines how the script depicts symptoms of schizophrenia, including hallucinations, delusions, and emotional instability. Additionally, the analysis investigates potential contributing factors such as neuropsychological vulnerabilities, immense pressure from ballet world, and a strained family dynamic. The Black Swan script serves as a valuable case study for understanding the complex interplay between internal and external forces that can trigger a mental illness. By examining Nina’s character, the study shed light on the challenges faced by individuals with schizophrenia and the importance of recognizing the diverse range of symptoms with the disorder.